2015
DOI: 10.1016/j.jaap.2015.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growth temperature and feedstock:catalyst ratio on the production of carbon nanotubes and hydrogen from the pyrolysis of waste plastics

Abstract: Carbon nanotubes have been produced from a low density polyethylene (LDPE) feedstock via a two stage pyrolysis process. The temperature of the second stage, where carbon deposition on an iron alumina catalyst occurs (growth temperature), was varied using catalyst temperatures of 700, 800 and 900 C. An increase in catalyst temperature led to a higher yield of both carbon nanotubes and hydrogen, as the rate of carbon deposition increased.Changing the amount of feedstock relative to the catalyst also had an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 71 publications
(105 reference statements)
6
56
0
2
Order By: Relevance
“…They showed that the quality of the product CNTs was influenced by catalyst temperature. We have also reported [19] the importance of catalyst temperature in determining the quality of CNTs from pyrolysis-catalysis of low-density polyethylene, with too high a temperature (900°C) distorting the product CNTs. Further, the influence of metal promoters in the nickel catalyst also affects the yield and quality of CNTs; for example, Fe and Co have been shown to promote CNT formation [20].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They showed that the quality of the product CNTs was influenced by catalyst temperature. We have also reported [19] the importance of catalyst temperature in determining the quality of CNTs from pyrolysis-catalysis of low-density polyethylene, with too high a temperature (900°C) distorting the product CNTs. Further, the influence of metal promoters in the nickel catalyst also affects the yield and quality of CNTs; for example, Fe and Co have been shown to promote CNT formation [20].…”
Section: Introductionmentioning
confidence: 93%
“…During the pyrolysis-catalysis of plastics, the polyalkene HDPE plastic was initially degraded into smaller organic compounds, then these compounds were dehydrogenated to produce carbon products and gaseous products [19]. The product oils and gases which are generated from the pyrolysis of the HDPE and which pass over the stainless-steel mesh catalyst have been analysed before and shown to be largely aliphatic in composition [29][30][31].…”
Section: Product Yieldmentioning
confidence: 99%
“…This techniques has been applied to characterize carbon type by many researchers [18,[29][30][31][32]. Figure 2(a) illustrates the TGA-TPO and the derivative rate of weight loss in relation to temperature programmed oxidation (DTG-TPO) results of the carbon on the used 10% Ni/Al2O3 catalyst.…”
Section: H2o + Co = H2 + Co2 Equationmentioning
confidence: 99%
“…%, with CH4 concentration decreasing from 22.12 to 17.81 vol.% and hydrocarbons C2-C4 markedly decreased in concentration. Acomb et al [32] investigated the influence of catalysis temperature on the production of carbon from the pyrolysis-catalysis of low density polyethylene and reported that more hydrogen and higher catalyst carbon deposition, including CNT's were produced as the temperature was increased.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Thermal recycling via pyrolysis and gasification of waste plastics, into fuels and chemical products has been identified as a promising technology for tackling waste issues related to plastics [2,3]. In recent years, an attractive method of producing high value nanomaterials such as carbon nanotubes (CNTs) from waste plastics has been reported [4,5]. The produced CNTs were further utilised to produce reinforced materials which exhibited improved strength characteristics, implying the potential of the process in industrial applications [6].…”
Section: Introductionmentioning
confidence: 99%